Fostering Students’ Academic Achievement in Physics through Graphic Organizer-Enhanced Learning Strategy - Uzomah, Theophilus N.; Achor, Emmanuel; Jack, Gladys U. (Papanda Publisher, 2024)
This study focused on fostering academic achievement in physics using graphic organizer-enhanced learning strategy among secondary students, Taraba State Nigeria. Two research questions and two hypotheses guided the study. The study adopted a quasi-experimental, research design. The sample for the study was 172 students comprising 113 males and 112 females drawn from secondary schools offering physics in Jalingo education zone. Data for the study were generated using Physics Achievement Test (PAT). Kuder Richardson-20 (K-20) formula was used for the reliability of PAT with index of 0.85 obtained. Mean, standard deviation and Analysis of Covariance (ANCOVA) were used for data analysis. The following findings emerged: There was significant difference in the mean score academic achievement in Physics of students taught using graphic organizer-enhanced learning strategy and those thought using the conventional strategy. There was significant difference in the mean score academic achievement in physics of male and female students taught using graphic organizer-enhanced learning strategy. It was recommended that Physics teachers should employ graphic organizer-enhanced learning strategy in their interaction when teaching physics as the strategy has the capacity to enhance male and female students’ academic achievement in physics. Physics teachers should regularly provide the structure and opportunity for students to employ graphic organizer-enhanced strategy in their learning process.